Restructuring Cultural Landscapes in Metropolitan Areas Characterization, Typology and Design Research - Xie, Yuting (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book introduces a ten-year-long design research project in the Yangtze River Delta (YRD), China, based on international cooperation studios, design workshops, a Ph.D. thesis, and concrete practice in China, Germany, and the Netherlands. This research adapts the existing methods of Landscape Character Assessment (UK), Historic Cultural Landscape Elements (Germany), and Dutch Polder Typology to mapping, describing, and classifying landscape character areas and types at the three scales of regional, municipal, and local. Furthermore, to connect research with design, we developed a typological approach of generating specific measures for the networked polder landscape. This research bridges the gap of a missing landscape characterization method for the conservation, transformation, and critical reconstruction of historic cultural landscapes in a metropolitan context. The book is intended for graduate students, researchers, and practitioners interested in the topics of cultural landscape in transition, methods for landscape characterization and typology, and a research-by-design approach in interdisciplinary projects of landscape architecture, urbanism, and regional planning.
Acknowledgments -- Summary -- Forward -- List of Figures -- List of Tables -- Chapter 1 Setting the Scene -- Chapter 2 Building the Research Context -- Chapter 3 Permanence and Resilience: The Framing Role of Landscape Architecture -- Chapter 4 Landscape Characterization and Typology: In Search of Methodology -- Chapter 5 Time, Space and Cultural Landscape: Morphogenesis of a Metropolitan Delta Landscape -- Chapter 6 Landscape Characterization, Typology, and Research-by-design -- Chapter 7 Conclusions and Discussion -- Appendices -- Appendix A Other Relevant Tables -- Appendix B Glossary of Chinese Terms -- Bibliography.
Keywords: Landscape architecture; Sustainable architecture; Architecture-History.; Urban policy; Landscape Architecture; Sustainable Architecture/Green Buildings; Architectural History and Theory; Urban Policy